2008
DOI: 10.1124/jpet.108.143560
|View full text |Cite
|
Sign up to set email alerts
|

Sensitization by 5-Azacytidine toward Death Receptor-Induced Hepatic Apoptosis

Abstract: 5-Azacytidine (5-aza-CR) is a DNA-hypomethylating antineoplastic agent used because of its inhibitory activity on DNA methyltransferases. Today, it is approved as an epigenetically active drug therapy for treatment of myelodysplastic disorders, with a contraindication as to pre-existing liver diseases. Because the mechanism of its hepatotoxicity is still unknown, we investigated the pharmacodynamic properties of 5-aza-CR with regard to death receptor/ligand-induced apoptosis and the mode of execution of cell d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
2
4
0
Order By: Relevance
“…In line with our result of a 5-aza-CR-mediated sensitisation to TRAIL, a recent report focusing on death receptor-induced apoptosis in general describes a sensitisation by 5-aza-CR towards death receptor-induced apoptosis 21. However, from a clinical perspective there are two major limitations of this work that would interfere substantially with a clinical translation of our suggested approach.…”
Section: Discussionsupporting
confidence: 78%
“…In line with our result of a 5-aza-CR-mediated sensitisation to TRAIL, a recent report focusing on death receptor-induced apoptosis in general describes a sensitisation by 5-aza-CR towards death receptor-induced apoptosis 21. However, from a clinical perspective there are two major limitations of this work that would interfere substantially with a clinical translation of our suggested approach.…”
Section: Discussionsupporting
confidence: 78%
“…In support of this observation is a recent report demonstrating that the antineoplastic agent 5-azacytidine sensitizes primary human and murine hepatocytes for death receptor-induced apoptosis. 25 Similarly, we have previously demonstrated that Fas-induced hepatocyte apoptosis and liver damage is strongly enhanced by TRAIL. 12 Furthermore, Koschny et al 26 described that primary human and murine hepatocytes are sensitized to TRAIL-induced apoptosis by the proteosome inhibitor bortezomib, though higher concentrations of bortezomib were needed than in hepatocellular carcinoma cells.…”
Section: Discussionmentioning
confidence: 69%
“…1). However, these clinical anticancer drugs are not ideal because of their induction of hepatotoxicity in cancer patients (46)(47)(48). Herein, we demonstrate that the cytotoxicity of HMDB is quite low in cancer cell xenograft mice, as determined by the examination of metabolic indices, body weight, and liver tissue in these mice (Fig.…”
Section: Discussionmentioning
confidence: 85%